2017
DOI: 10.1371/journal.pone.0187791
|View full text |Cite
|
Sign up to set email alerts
|

Respective impact of implementation of prevention strategies, colonization with multiresistant bacteria and antimicrobial use on the risk of early- and late-onset VAP: An analysis of the OUTCOMEREA network

Abstract: RationaleThe impact of prevention strategies and risk factors for early-onset (EOP) versus late-onset (LOP) ventilator-associated pneumonia (VAP) are still debated.ObjectivesTo evaluate, in a multicenter cohort, the risk factors for EOP and LOP, as the evolution of prevention strategies.Methods7,784 patients with mechanical ventilation (MV) for at least 48 hours were selected into the multicenter prospective OUTCOMEREA database (1997–2016). VAP occurring between the 3rd and 6th day of MV defined EOP, while tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
0
12
0
2
Order By: Relevance
“…E1). The VAP prevention policy was similar between ICUs and is described elsewhere [23]. Subglottic aspiration was not used as routine practice.…”
Section: Take-home Messagementioning
confidence: 99%
“…E1). The VAP prevention policy was similar between ICUs and is described elsewhere [23]. Subglottic aspiration was not used as routine practice.…”
Section: Take-home Messagementioning
confidence: 99%
“…Peptic ulcer prophylaxis was the most performed measure in this study in 85.2% of the observations. Studies have found the non-use (24) and adhesions to this measure between 56.0% (19) and 100% (22) . This measure can be challenged in practice, since the risks and benefits of its application to the patient should be weighed.…”
Section: Discussionmentioning
confidence: 99%
“…This finding corroborates national studies in which the VAP prevalence was 23.2% (14) and 31.8% (15) . International studies have shown that VAP incidence varies from 8.0% to 25.0%, reaching 31.0% in the United States (19)(20) . The difference in these findings can be attributed to the diagnostic criteria for VAP, which may under or overestimate this condition (21) .…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Whereas VAP bundles appear effective in reducing early-onset VAP (occurring within 5-7 d), late-onset VAP seems associated with patient severity and is thus more difficult to prevent. 17 The occurrence of VAP has been associated with several pathophysiological mechanisms, but a simplified paradigm is based on the presence of pathogens penetrating the lungs from within the ETT and around the ETT cuff, mainly from the digestive tract. 18 Preventive measures are usually based on the reduction of pathogen burden from one or both of the two reservoirs.…”
Section: Introductionmentioning
confidence: 99%